ANALISIS KESULITAN BELAJAR SISWA KELAS II PADA MATERI PENJUMLAHAN DI SD NEGERI SERANG 06 - Indah, Juwita; Wijaya, Sastra; Rahayu, Maulina (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to analyze the learning difficulties experienced by second-grade students at SDN Serang 06 in mastering addition, which serves as the foundation for subsequent mathematical operations. Using a qualitative descriptive approach, the research involved students and classroom teachers as subjects, with data collected through observation, interviews, and documentation, and validated using triangulation techniques. The findings reveal four main types of difficulties: (1) conceptual difficulties in understanding addition as a process of combining numbers; (2) procedural difficulties, particularly in column addition with carrying; (3) difficulty recalling basic addition facts, indicated by reliance on finger counting; and (4) difficulty solving word problems due to inability to link problem contexts with appropriate operations. Contributing factors include internal aspects such as anxiety, low motivation, and lack of confidence, as well as external aspects like monotonous teaching methods, limited media use, and insufficient parental support. The study highlights the need for innovative learning strategies utilizing concrete and contextual media, along with teacher–parent collaboration, to minimize learning difficulties and strengthen students’ mathematical foundations.